ANALISA PERBANDINGAN KEKUATAN DESAIN ADHESIVE JOINT PADA MATERIAL FRP MENGGUNAKAN METODE ELEMEN HINGGA - Rena Riza Umami; Budianto Budianto; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2020)
Damage on FRP Ships in Indonesia is quite common. Damage was often occurs in the hull-deck joint area.The hull-deck joint of the FRP ship is an important thing in reference to the quality and structural strength of the FRP ship. Currently, researchers research about hull-deck joint method of FRP ships in order to obtain the proper joint method and result of joint according to the material and use of a structure.An example of a joint method that is often used especially in composite materials is the adhesive joint method. In the adhesive joint method, the right type of adhesive is a very influential part of the structural strength of a joint. This final project is focused on analyzing and comparing several joint designs for FRP material where examples of its application are on the hull and deck joints of FRP ships to find out which design are the best structural strength using ANSYS software. The simulation results of 45,000 N load shear stress obtained a shear strength value of 470.60 MPa for designs with epoxy film(design 1), 470.69 MPa for designs with epoxy(design 2),and 470.72 MPa for designs with a polyester(design 3). Through manual calculation and analysis, the joints with polyester are best.